2007
DOI: 10.1109/iembs.2007.4353411
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations for a Personalized Wheelchair Navigation System

Abstract: Individuals with mobility impairments such as wheelchair users are often at a disadvantage when traveling to a new place, as their mobility can be easily affected by environmental barriers, and as such, even short trips can be difficult and perhaps impossible. We envision a personalized wheelchair navigation system based on a PDA equipped with wireless Internet access and GPS that can provide adaptive navigation support to wheelchair users in any geographic environment. Requirements, architectures and componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 10 publications
0
29
0
1
Order By: Relevance
“…Based on the specification, some of the recommended parameters that need to be implemented in the final dataset can be surface information, incline and width of the sidewalk segment. However, based on a number of other studies [29,[37][38][39], additional parameters for a disabled friendly routing network have been determined which would are later introduced in Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the specification, some of the recommended parameters that need to be implemented in the final dataset can be surface information, incline and width of the sidewalk segment. However, based on a number of other studies [29,[37][38][39], additional parameters for a disabled friendly routing network have been determined which would are later introduced in Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…Travelling is a laborious task for wheelchair users, especially in unfamiliar environments, because they have to overcome an array of interpersonal and environmental barriers (Ding et al 2007, Volkel et al 2008. In a study conducted by Meyers et al (2002), 28 adult wheelchair users were interviewed and it was found that the barriers frequently reported included narrow sidewalks, no ramps or steep ramps, no sidewalk curb cuts, poor sidewalk surfaces and sidewalk obstructions.…”
Section: Introductionmentioning
confidence: 99%
“…Design considerations for personalized wayfinding and navigation technology for WCU were discussed in [31] but no comprehensive system has been developed yet. Key considerations of the design include: requirements that the map database include location-based accessibility features, such as sidewalk conditions; personalized route planning algorithms that can be accomplished based on the users functional level and preferences; and positional accuracy within 3 meters.…”
Section: Wheelchair Usersmentioning
confidence: 99%
“…U-Access included features which address all three of the design considerations discussed in [31]. An 'individuals physical ability level' was codified as either peripatetic, aided mobility, or wheelchair user.…”
Section: Single-site Wayfinding Systems For Wheelchair Usersmentioning
confidence: 99%
See 1 more Smart Citation